Pengaruh Kepemimpinan Islami dan Budaya Organisasi Islami Terhadap Motivasi Kerja Islami Pada UMKM Kulit di Magetan - Aziz, Rezy; Shofawati, Atina (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of this research is to know the effect of islamic leadership and islamic organization culture in variable through islamic work motivation to SMEs leather in Magetan.This research uses questionnaires in primary data collected and the method used is quantitative descriptive by using two independent variables islamic leadership and islamic organization culture and a dependent variable islamic work motivation. Research sampling is the employee of SMEs leather in Magetan industry area in east java, it was 110 people. Sampling collected takes in proportioned stratified random sampling because each SMEs leather will be taken a random sampling. Data analysis technique used is multiple linear regression analysis by using F and T treatment as hypothesisThe results showed that simultaneous and partial Islamic leadership and Islamic organizational culture influence significant on Islamic work motivation.